Schaum's outlines geometry - Rich, Barnett, 1906-; Thomas, Christopher 1973- (New York : McGraw-Hill, 2013)
Lines, angles, and triangles -- Methods of proof -- Congruent triangles -- Parallel lines, distances, and angle sums -- Parallelograms, trapezoids, medians, and midpoints -- Circles -- Similarity -- Trigonometry -- Areas -- Regular polygons and the circle -- Locus -- Analytic geometry -- Inequalities and indirect reasoning -- Improvement of reasoning -- Constructions -- Proofs of important theorems -- Extending plane geometry into solid geometry -- Transformations -- Non-Euclidean geometry -- Formulas for reference -- Answers to supplementary problems.